Exploring the link between anabolic-androgenic steroids abuse for performance improvement and hepatocellular carcinoma: a literature review - Coelho, Rafael Corrêa; dos Santos Fernandes, Gustavo; Sternberg, Cinthya (Brazilian Journal of Oncology, 2018)
Introduction: Hepatocellular carcinoma (HCC) corresponds to 90% of primary malignant liver cell carcinomas and is a leading cause of cancer-related death worldwide.Objective: This compilation of cases aimed to identify evidence of correlation between anabolic androgen steroids (AAS) abuse for performance improvement by healthy subjects and HCC.Methods: We performed a literature review and identified 935, 1148, 12 and 3 articles in Pubmed, Embase, Scopus and Lilacs, respectively. Only studies, reviews and case reports evaluating the association between androgens and hepatocarcinoma were included with no restrictions in time span or language. Further on, we excluded studies and case reports which patients were receiving therapeutic androgens and collected data only of those reporting androgen intake to improve physical performance.Results: Six articles fulfilled the inclusion criteria, excluding the duplicates. HCC onset after AAS abuse seems to occur at earlier ages than those related to chronic hepatitis B/C, chronic alcohol consumption and nonalcoholic steatohepatitis (NASH). Timeframe ranged from two to seven years in the cases reports presented here. Many AAS subtypes were used by patients depicted in the case reports, so it is difficult to conclude if a specific AAS is safer or more harmful than the other. Carcinogenic mechanisms are poorly understood, but pre-clinical evidence shows that androgen receptors and oxidative stress may play a pivotal role in its development.Conclusion: The evidence that HCC has been linked to long term AAS abuse for performance improvement is scant but some association is suggested. AAS must be taken only under specialized supervision and the putative correlation with HCC calls for public policies to make high risk populations aware of the risks of misuse and self-administration.
Keywords: Hepatocellular carcinoma; Anabolic androgen steroids; Testosterone congeners